LITERASI MEDIA SEBAGAI KUNCI SUKSES GENERASI DIGITAL NATIVES DI ERA DISRUPSI DIGITAL - Frederik Masri Gasa; Eflina Nurdini Febrita Mona (Universitas Prof. Dr. Moestopo (Beragama), 2020)
In the era of digital disruption, internet is a major differentiating factor in the social arena of society. The internet presents various forms of new media platforms which known as digital media or social media. Social media has become a media information and at the same time as a new employment for the community, especially for the digital natives. This generation knows the internet and social media since they were little kids and over time, they are able to change social media from just channeling a hobby to become a profitable media. This cleverness in reading business opportunities is also due to the strong foundations of media literacy that were acquired since they were young. This happened to the six students in Malang who were informants in this study. Researchers used a qualitative approach with an interpretive paradigm to be able to explore how the background of these six students in achieving profits through the social media.